Implementation of Right to Service: A Study of SAS (Sahibzada Ajit Singh) Nagar District, Punjab - Singh, Harmanpreet (Indian Journal of Public Administration, 2024)
This article is based on an empirical study and deals with the service users of Sewa Kendras and Saanjh Kendras in the SAS Nagar district of the Punjab state. The article relates to the viewpoints of the service users of Sewa and Saanjh Kendras to assess the perceptions of service users regarding the implementation of the Punjab Right to Service Act, 2011, in the SAS Nagar district. By perception, it tries to figure out the awareness and satisfaction levels of service users regarding the delivery of services at these Kendras working under the Punjab Right to Service Act, 2011. In order to form an estimate of the perception of the service users, an interview schedule was administered to a randomly selected sample of 300 citizens, who were receiving services at Sewa and Saanjh Kendras of all the Tehsils of the SAS Nagar district.
Keywords: Public Service Delivery; Right to Service; Saanjh Kendra; Sewa Kendra; Public Administration